2021
DOI: 10.1002/fsn3.2169
|View full text |Cite
|
Sign up to set email alerts
|

Assessing of growth, antioxidant enzymes, and phytohormone regulation in Cucurbita pepo under cadmium stress

Abstract: One of the major problems worldwide is soil pollution by trace metal elements, which limits plant productivity and threatens human health. In this work, we have studied the effect of different concentrations of cadmium on Cucurbita pepo plants, evaluating different physiological and biochemical parameters: hormone signaling, metabolite concentration (malondialdehyde and hydrogen peroxide) and, in addition, the antioxidant enzyme activities of catalase and superoxide dismutase were evaluated. The production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 60 publications
7
21
0
Order By: Relevance
“…In plants, metallic ions may have a different distribution rate, so some TME are immobilized and accumulated in root tissues such as Cd (Labidi et al., 2021), Fe (Roshani et al., 2014), As (Raab et al., 2007) and Al (Fan et al., 2020). Other cations, like Ba, are more freely transported to the aerial parts (Sleimi et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In plants, metallic ions may have a different distribution rate, so some TME are immobilized and accumulated in root tissues such as Cd (Labidi et al., 2021), Fe (Roshani et al., 2014), As (Raab et al., 2007) and Al (Fan et al., 2020). Other cations, like Ba, are more freely transported to the aerial parts (Sleimi et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The extraction was achieved via a heated attack using six different acid digestion methods: nitric-sulfuric-perchloric acid digestion (method C) in a proportion of 10:1:0.5, v/v/v [8,9]; hydrochloric-nitric acid digestion, known as aqua regia mixture (method D), in a proportion of 3:1, v/v [10]; nitric-perchloric acid digestion (method E) in a proportion of 3:1, v/v [11]; nitric-sulfuric acid digestion (method F) in a proportion of 2:1, v/v [12]; nitrichydrochloric-perchloric acid digestion (method G) in a proportion of 5:1:0.5, v/v/v [13], and nitric-hydrochloric-sulfuric acid digestion (method H) in a proportion of 5:1:1, v/v/v [14].…”
Section: Acid Mixtures Digestionmentioning
confidence: 99%
“…However, studies by Idera et al [7] have reported that the use of mixtures of acids is generally fast and more efficient, and the most commonly used are nitric (HNO 3 ), sulfuric (H 2 SO 4 ), perchloric (HClO 4 ) and hydrochloric (HCl) acids, as well as hydrogen peroxide. For the extraction of metals from plant tissues, a variety of acid mixtures have been used, such as a nitric-sulfuric-perchloric acid mixture (10:1:0.5, v/v/v) [8,9]; hydrochloric-nitric acids known as aqua regia mixture (3:1, v/v) [10]; nitric-perchloric acid mixture (3:1, v/v) [11]; nitric-sulfuric acid mixture (2:1, v/v) [12]; nitric-hydrochloric-perchloric acid mixtures (5:1:0.5, v/v/v) [13] and nitric-hydrochloric-sulfuric acid mixtures (5:1:1, v/v/v) [14]. The choice of an individual acid or a combination of acids depends on the nature of the matrix to be decomposed [14].…”
Section: Introductionmentioning
confidence: 99%
“…At the end of the experiments, treated plants were collected and split into two parts: shoots and roots. The shoots were rinsed with distilled water, while the roots were rinsed with CaCl 2 5% [ 26 , 27 , 28 ] to remove trace elements adsorbed on the root surface and washed twice with distilled water.…”
Section: Methodsmentioning
confidence: 99%